An efficient approach to the synthesis of 7-thioxosubstituted [1, 3]thiazolo[3, 2-c]pyrimidines and evaluation of their antimicrobial and antioxidant activities. (2nd January 2022) - Litvinchuk, Mariia B.; Bentya, Anton V.; Stasevych, Maryna V.; Zvarych, Viktor I.; Komarovska-Porokhnyavets, Olena Z.; Stadnytska, Nataliya E.; Lubenets, Vira I.; Rusanov, Eduard B.; Vovk, Mykhailo V.
Abstract: A preparatively convenient one-pot method for the synthesis of new 7-thioxo[1, 3]thiazolo[3, 2- c ]pyrimidine derivatives 3a–3l by the cyclocondensation of 5-methyl(1, 3-thiazolidin-2-ylidene)ketones 1a–1c with aroyl 2a–2d and 2-thienyl 2e isothiocyanates for 6–10 h boiling in acetone has been developed. Studies of the antimicrobial and antioxidant activities potential of the obtained compounds revealed that [2-methyl-5-(4-nitrophenyl)-7-thioxo-2, 3-dihydro-7 H -[1, 3]thiazolo[3, 2- c ]pyrimidine-8-yl](phenyl)methanone 3k, effect on the test culture of M. luteum at a concentration of 0.5% is close to the control drug vancomycin. Moreover, [5-(4-bromophenyl)-2-methyl-7-thioxo-2, 3-dihydro-7 H -[1, 3]thiazolo[3, 2- c ]pyrimidin-8-yl](phenyl)methanone 3j has an antibacterial effect on the specified test culture at a minimum inhibitory concentration of 15.6 μg/mL. In turn, 1-(2-methyl-5-(thiophen-2-yl)-7-thioxo-2, 3-dihydro-7 H -[1, 3]thiazolo[3, 2- c ]pyrimidin-8-yl]ethanone 3d can be considered promising for further structural modification to enhance the antioxidant effect. The structure of all synthesized substances was established by spectral analysis ( 1 H and 13 C NMR, LC–MS, and FT-IR). Additionally, the structure of compound 3i was confirmed by X-ray diffraction analysis. Graphical Abstract: UF0001